Urbanisation, land use, land degradation, and environment - International Workshop on "Urbanization, Land Use, Land Degradation, and Environment" (2009 Denizli İli, Turkey); Öztürk, Münir A. (Münir Ahmet); Mermut, A.R. (Ahmet R.); Celik, Ali; Pamukkale Üniversitesi; Türkiye Bilimsel ve Teknolojik Araştırma Kurumu; Centre for Science and Technology of the Non-Aligned and Other Developing Countries (Delhi Daya Pub. House, 2011)
Papers presented at the International Workshop on "Urbanization, Land Use, Land Degradation and Environment", jointly organized by Pamukkale University, Turkish Scientific and Technical Research Organization and the Center for Science and Technology of the Non-Aligned and Other Developing Countries during 28th September-1st October 2009 in Denizli, Turkey.
"Denizli Municipility; Pamukkale University; Scientific and Technological Research Council of Turkey; Centre for Science & Technology of the Non-Aligned and Other Developing Countries."
Keywords: Urbanization -- Congresses; Land use -- Congresses; Land degradation -- Congresses; Environmental policy -- Congresses